2019
DOI: 10.1097/01.aoa.0000557646.27382.36
|View full text |Cite
|
Sign up to set email alerts
|

The Intrapartum and Perinatal Risks of Sleep-disordered Breathing in Pregnancy: A Systematic Review and Meta-Analysis

Abstract: CondensationSleep disordered breathing is associated with a higher risk of adverse intrapartum and perinatal outcomes. Short TitleSleep disordered breathing in pregnancy -Systematic review and meta-analysis Implications and Contributions• This study was conducted to evaluate a common sleep disorder that is increasingly prevalent in pregnancy given the rise in maternal obesity rates.• The results clearly indicate that intrapartum and perinatal outcomes in women with sleep-disordered breathing are significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
(206 reference statements)
1
4
0
Order By: Relevance
“…While self-assessments or screening tools for OSA have independently been shown to be predictive of PTD, they have not included the STOP questionnaire. Our finding of a positive STOP screen predicting NICU admissions, with an OR of 2.5, is similar to the results of a study that found women with sleep disorder breathing had a higher rate of infants admitted to the NICU (OR = 1.90; CI: 1.38-2.61) 7 and a systematic review reporting a significant association between sleep disorder breathing and NICU admission (OR = 2.43; 95% CI, 1.61-3.68; p < 0.001). 8 This study is an example of finding reasonable association between the screening tool and outcome, but screening performance is too low and therefore does not pass the test of being a worthwhile screening tool.…”
Section: Discussionsupporting
confidence: 89%
“…While self-assessments or screening tools for OSA have independently been shown to be predictive of PTD, they have not included the STOP questionnaire. Our finding of a positive STOP screen predicting NICU admissions, with an OR of 2.5, is similar to the results of a study that found women with sleep disorder breathing had a higher rate of infants admitted to the NICU (OR = 1.90; CI: 1.38-2.61) 7 and a systematic review reporting a significant association between sleep disorder breathing and NICU admission (OR = 2.43; 95% CI, 1.61-3.68; p < 0.001). 8 This study is an example of finding reasonable association between the screening tool and outcome, but screening performance is too low and therefore does not pass the test of being a worthwhile screening tool.…”
Section: Discussionsupporting
confidence: 89%
“…SDB during pregnancy has been related to adverse fetal outcomes including preterm birth, fetal growth restriction (FGR) and neonatal intensive care unit admission (Brown et al . 2018; Warland et al . 2018 b ; Liu et al .…”
Section: Introductionmentioning
confidence: 99%
“…SDB encompasses a spectrum of disorders ranging from snoring to partial or complete obstruction of the upper airway repeatedly during sleep, resulting in sleep disruption and hypoxaemia. SDB during pregnancy has been related to adverse fetal outcomes including preterm birth, fetal growth restriction (FGR) and neonatal intensive care unit admission (Brown et al 2018;Warland et al 2018b;Liu et al 2019), but as yet no strong links have been established between SDB and stillbirth (Louis et al 2014;Bin et al 2016;Spence et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…4 OSA was reported to be associated with maternal complications like cardiomyopathy, congestive heart failure, pulmonary embolism and metabolic disorders including gestational diabetes mellitus (GDM), pregnancy induced hypertension(PIH), 4 maternal obesity, and preeclampsia, 5 and to increase the incidence of elective and emergency caesarean deliveries and assisted vaginal deliveries. 6 Adverse foetal/ neonatal outcomes include foetal growth restriction, foetal hypoxia, neonatal hyperbilirubinemia, 7 low APGAR score, 1 preterm births, 6,8 low birth weight (LBW), 9 and stillbirth/ perinatal death and neonatal intensive care unit (NICU) admissions. 6 These evidences suggest that early detection and management of OSA during pregnancy are likely to improve pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…6 Adverse foetal/ neonatal outcomes include foetal growth restriction, foetal hypoxia, neonatal hyperbilirubinemia, 7 low APGAR score, 1 preterm births, 6,8 low birth weight (LBW), 9 and stillbirth/ perinatal death and neonatal intensive care unit (NICU) admissions. 6 These evidences suggest that early detection and management of OSA during pregnancy are likely to improve pregnancy outcomes. The gold standard for diagnosis of OSA is polysomnography 10 but performing this is not always feasible due to cost and logistical constraints.…”
Section: Introductionmentioning
confidence: 99%